2022
DOI: 10.1007/s00213-021-06057-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of episodic future thinking on reinforcement pathology during smoking cessation treatment among individuals with substance use disorders

Abstract: Rationale Reinforcer pathology (RP) is a theoretical model based on two processes: delay discounting (DD) and drug demand. Given that RP has been shown to have a predictive value on smoking behaviors, several studies have explored which interventions can reduce RP. Consistent with the RP framework, episodic future thinking (EFT) has shown effects on treatment outcomes and RP processes. The vast majority of studies that assess the effects of EFT on RP consist of experimental studies, and no previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
0
8
0
2
Order By: Relevance
“…EFT event timeframes into the future differed across studies and ranged from 1 day (e.g., Snider et al, 2016) to 10 years (Nan & Qin, 2019) for the shortest delay and between 3 months (García-Pérez et al, 2022) and 25 years for future delays (Snider et al, 2021). The most common control condition was episodic recent thinking (ERT), in which individuals recall various time points in the past ( n = 11 studies; 69%).…”
Section: Resultsmentioning
confidence: 99%
“…EFT event timeframes into the future differed across studies and ranged from 1 day (e.g., Snider et al, 2016) to 10 years (Nan & Qin, 2019) for the shortest delay and between 3 months (García-Pérez et al, 2022) and 25 years for future delays (Snider et al, 2021). The most common control condition was episodic recent thinking (ERT), in which individuals recall various time points in the past ( n = 11 studies; 69%).…”
Section: Resultsmentioning
confidence: 99%
“…Recent meta-analyses show EFT could effectively reduce DD, although inconsistent results are reported (Rösch et al, 2021; Ye et al, 2021). Specifically, research has demonstrated EFT can reduce DD among individuals using substances (e.g., Bulley & Gullo, 2017; Forster et al, 2021; García-Pérez et al, 2022; Mellis et al, 2019; Patel & Amlung, 2020; Snider et al, 2016; Sofis et al, 2020; Stein et al, 2016, 2018). Similar effects have been found on alcohol demand (Bulley & Gullo, 2017; Meshesha et al, 2020; Patel & Amlung, 2020; Snider et al, 2016).…”
Section: Episodic Future Thinkingmentioning
confidence: 99%
“…Con respecto al número de prácticas necesarias, la evidencia más reciente sugiere que una mayor práctica del PEF tiene un mayor impacto sobre el DD, tanto en consumidores de sustancias (García-Pérez et al, 2022;Mellis et al, 2019), como en personas con obesidad (Mansouri et al, 2020), aumentando el efecto sobre el DD a medida que aumentan el número de sesiones. Con relación al formato de aplicación, el PEF se ha implementado mayoritariamente en un formato cara a cara, aunque recientemente se ha evaluado su factibilidad en formato online (Sofis et al, 2020;Sze et al, 2015).…”
Section: Tabla 1 Ejemplos De Políticas De Salud Pública Basadas En El...unclassified
“…Por otro lado, aunque el PEF ha sido llevado a cabo principalmente de forma aislada, algunos estudios lo han combinado con otros tratamientos (p.ej., terapia cognitivo conductual, manejo de contingencias) obteniendo excelentes resultados (García-Pérez et al, 2022).…”
Section: Tabla 1 Ejemplos De Políticas De Salud Pública Basadas En El...unclassified